(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Periodically, educational changes and advancements are necessary to align with the global educational landscape and to enhance innovative ideas and thoughts for the improvement of quality education.The NEP 2020 introduced by the Government of India heralds a significant paradigm shift in the educational landscape, aiming to overhaul the existing framework to align with the dynamic needs of the 21st century. The policy includes elementary education to higher education in both rural and urban in India. The first NPE was proclaimed by the Government of Indiaby Indira Gandhiformer PM of India in 1968, the second NEP adopted by former PM Mr. Rajiv Gandhi in 1986, and the third NEP by Hon’bleP.M. Narendra Modi in 2020. Education is a fundamental instrument for achieving potential excellence, developing an equitable society and promoting national development. The NEP2020 acknowledges the importance of teachers and training in delivering high –quality content and pedagogy, teacher education will gradually be moved by 2030 into multidisciplinary colleges and universities. All the colleges and universities will move towards multidisciplinary, it has aim todevelop as outstanding education departments that offer B.Ed., M.Ed., and Ph.D. degrees in education. This studyan initiative has taken to highlight on NPE 2020 and its Quality Learning Outcomes inTeacher Training Institutions.